On time-resolved electron emission at the attosecond time scale. (November 2015) - Gao, C-Z; Dinh, P M; Reinhard, P-G; Suraud, E
Abstract: We investigate from a theoretical perspective time-resolved photoionization of N2 irradiated by a combination of a long infrared (IR) pulse with a dedicated train of attosecond pulses (APT) in the extreme ultraviolet (XUV) range. The delay time of the attosecond train with respect to the infrared pulse is systematically varied, in accordance with experiments. We find marked oscillations of the ionization yield as a function of delay. We analyze the position of maxima and minima of electron yield and trends with XUV frequency.